Research Progress in Thermal Runaway Vent Gas Characteristics of Li-Ion Battery - Mingming Qiu; Jianghong Liu; Beihua Cong; Yan Cui (Batteries, 2023)
The wide application of lithium-ion batteries (LIBs) brings along with it various safety problems, such as fire and explosion accidents. Aiming at the thermal runaway (TR) and fire problems of LIBs, we reviewed the evolution of TR within LIB and the release of TR gases and their hazards, as well as the research progress in recent years in the area of fire separation of LIBs. To begin with, physical, electrical, and thermal abuse are the three main factors leading to TR and the thermal stability of aging batteries significantly deteriorates. Furthermore, the decomposition of the electrolyte and the reaction between the active materials generates CO, CO2, H2, HF, and a variety of hydrocarbons. These TR gases have serious toxic and explosive hazards. In addition, fire separation can effectively delay the occurrence and propagation of TR within LIB modules. As a good heat-absorbing material, phase-change materials are widely used in the thermal management system and have a great prospect of wide applications in the fire separation of LIBs. Finally, the research on the TR gases’ hazards of aging LIB and safer and more effective fire separation are prospected.